Toward a Grotkean Pedagogy: Teacher as Political - Golden, Sean Cameron (Radical Teacher, 2023)
Teachers, and teaching, are not supposed to be political. For years this mantra was said and believed to be true. Whenever political queations were encountered in the classroom, teachers, according to the white male patriarchy that shaped modern day schooling, were expected to push those questions aside and continue to teach the "content" dictated by the heteropatriarchal system of public schools. Inspired by Miss Alordayne Grotke’s teaching from the Disney show Recess!, this autoethnographic work explores how and why I chose to practice being teacher as political. This article narrowly focuses on specific political choices made inside the classroom and debunks the myth that a teacher should be politically neutral in the classroom.